The Role of the Gresik District Education Office in Improving the Quality of Educational Services at UPT SD Negeri 81 Gresik - Fitriana, Lilis; Arundinasari, Indira (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
This study examines the role of the Gresik District Education Office in improving the quality of educational services at UPT SD Negeri 81 Gresik. Using a descriptive qualitative approach, data were collected through observation, interviews, and document analysis. The analysis is based on Jones's theory of government roles, specifically the regulatory role, the enabling role, and the direct provision of goods and services. The findings show that in its regulatory role, the Education Office has implemented national policies, such as the Merdeka Curriculum and the Education Report, as instruments for quality evaluation. In the enabling role, the Education Office contributes through teacher capacity building, collaboration with higher education institutions, and cross-sector advocacy for school relocation. In the role of direct provision of goods and services, the Education Office facilitates the provision of learning technology devices. It is concluded that the role of the Gresik District Education Office in improving the quality of educational services at UPT SD Negeri 81 Gresik has been implemented but has not yet been fully effective, particularly in addressing the school's structural and geographical challenges.